Laser Scribing for Perovskite Solar Modules of Long-Term Stability - Jeong, Yujin; Kim, Yejin; Lee, Hanseul; Ko, Seoyeon; Ham, Seung Sik; Jung, Hye Ri; Choi, Jun Hwan; Kim, Won Mok; Jeong, Jeung-hyun; Yoon, Seokhyun; Hwang, David J.; Kim, Gee Yeong (WILEY-V C H VERLAG GMBH, 2024)
Although the efficiency of hybrid lead-halide perovskite solar cells has been significantly improved, the efficiency gap between small-area cells and large modules continues to be a considerable challenge. Laser scribing is essential for realizing high-quality monolithic connections; however, the laser-induced material changes and their correlation with device performance have not been yet well understood, in particular for the perovskite material systems. In this study, the effect of P3 laser processing conditions on device performance and stability is explained. The most interesting finding is an improvement in open-circuit voltage (VOC) after aging and long-term stability under low-laser-overlap conditions that avoid direct laser exposure to perovskite material system as a source of material degradation. It is found that a high-laser-overlap during P3 results in a lower fill factor after aging and accelerated degradation due to larger portion of perovskite directly exposed to laser during the scribing process. The increased VOC under low-overlap conditions is attributed to the increased PbI2 formation in the P3 region. Moreover, a minimal pulse overlap is favorable for preserving long-term device stability. Finally, a perovskite minimodule with an efficiency of 20.24% is successfully developed as a result of these findings. Here, the optimal P3-laser-scribing parameters are explored and the efficiency loss and long-term stability induced by P3 scribing are demonstrated. By reducing the degree of laser overlap, an enhancement of open-circuit voltage was observed after aging and better long-term stability of perovskite module. Using an all-laser-scribing method, a high-performance perovskite solar module was successfully fabricated with an efficiency of 20.24%.image (c) 2024 WILEY-VCH GmbH